Discovering John : essays by John Ashton - Ashton, John, 1931-2016 (James Clarke & Co, 2021)
"The renowned Johannine scholar John Ashton (1931-2016) left a large number of unpublished essays at the end of his life, representing his ongoing exegetical work. Introduced here by Christopher Rowland and Catrin H. Williams, they explore important themes such as mystery and Christology arising from his ground-breaking study, Understanding the Fourth Gospel. Alongside them is an intellectual autobiography originally intended for that volume, contextualizing Ashton's work both in the wider context of biblical scholarship and the particularities of his life. This in itself is an exceptional contribution, and together with the essays it sheds light not only on the current state of Johannine studies, but also on the situation of those involved with both church and academy in the closing decades of the twentieth century"--Back cover.